Assessment indicators in university extension curriculum: proposal for business and accounting courses - Silva, Luciane Duarte da; Vieira, Almir Martins; Tambosi Filho, Elmo (Avaliação : revista da Rede de Avaliação Institucional da Educação Superior, 2024)
Abstract With the publication of Resolution CNE/CES nº 7 of 2018, which deals with the curricularization of extension, Higher Education Institutions (HEIs) were mobilized to comply with the guidelines established in that document. Given this scenario, this article aims to present some possibilities of indicators that can be used as a reference by professors of Administration and Accounting courses at HEIs in their extension actions. In addition to the implementation of the extension curricularization, it is also reflected on the evaluation of such actions. In methodological terms, a qualitative approach was taken, in a documentary research, based on the following documents: Resolution CNE/CES nº 7 of 2018, National Extension Policy of the Forum of Pro-Rectors for Extension of Public Institutions of Higher Education in Brasil and the announcement of the Federal University of ABC (UFABC). The results described dialogue with the current literature on the subject and advance towards a better understanding of the extension evaluation processes, especially for professors and coordinators of Administration and Accounting courses, in order to enable the systematization of extension actions, as well as allow the student to be the protagonist in the extension activities. Resumo Com a publicação da Resolução CNE/CES nº 7 de 2018, que trata da curricularização da extensão, houve mobilização das Instituições de Ensino Superior (IES) para o atendimento das diretrizes estabelecidas no referido documento. Diante deste cenário, este artigo tem como objetivo apresentar algumas possibilidades de indicadores que podem ser utilizados como referência por docentes dos cursos de Administração e Contabilidade nas IES em suas ações extensionistas. Além da implantação da curricularização da extensão, reflete-se também sobre a avaliação de tais ações. Em termos metodológicos, assumiu-se abordagem qualitativa, em pesquisa de caráter documental, com base nos seguintes documentos: Resolução CNE/CES nº 7 de 2018, Política Nacional de Extensão do Fórum de Pró-Reitores de Extensão das Instituições Públicas de Educação Superior Brasileiras e o edital da Universidade Federal do ABC (UFABC). Os resultados descritos dialogam com a literatura atual sobre o tema e avançam para maior compreensão sobre os processos de avaliação da extensão, em especial para professores e coordenadores de cursos de Administração e Contabilidade, no sentido de possibilitar a sistematização das ações de extensão, bem como permitir que o estudante seja protagonista nas atividades de extensão. Resumen Con la publicación de la Resolución CNE/CES nº 7 de 2018, que trata de la curricularización de la extensión, hubo movilización de las Instituciones de Educación Superior (IES) para atender a las directrices establecidas en ese documento. Ante este escenario, este artículo tiene como objetivo presentar algunas posibilidades de indicadores que pueden ser utilizados como referencia por los profesores de los cursos de Administración y Contabilidad de las IES en sus acciones extensionistas. Además de la implementación de la curricularización de la extensión, también se reflexiona sobre la evaluación de tales acciones. En términos metodológicos, se asumió enfoque cualitativo, en investigación de carácter documental, con base en los siguientes documentos: Resolución CNE/CES nº 7 de 2018, Política Nacional de Extensión del Foro de Pro-Rectores de Extensión de las Instituciones Públicas Brasileñas de Educación Superior y las directrices de la Universidad Federal del ABC (UFABC). Los resultados descritos dialogan con la literatura actual sobre el tema y avanzan para una mayor comprensión sobre los procesos de evaluación de la extensión, especialmente para profesores y coordinadores de cursos de Administración y Contabilidad, de forma a posibilitar la sistematización de las acciones de extensión, así como permitir que el alumno sea protagonista en las actividades de extensión.